PENYEDIAAN KOLEKSI DALAM MEMENUHI KEBUTUHAN INFORMASI PENGGUNA DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA PADANG - Dola, Regita Tri (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2024)
This study aims to analyse the availability of library material collections at the Padang City Library and Archives Office in meeting the information needs of users. The method used is a qualitative approach with literature study as the basis for data collection. Public libraries act as information centres, sources of knowledge, and recreational facilities aimed at the wider community. The availability of collections is one of the main indicators of the library's success in fulfilling information needs, which include cognitive, affective, personal integration, social integration, and fantasy needs. The results show that the library has tried to provide a relevant, up-to-date and diverse collection, based on the analysis of library users' needs and the frequency of use of the collection. In addition, the librarian's cooperation with various parties also supports the optimal collection procurement process. However, challenges in terms of collection completeness and management are still a concern. This study provides important recommendations for libraries to continue improving collection procurement strategies to increase utilisation. Translated with DeepL.com (free version).